Challenges and Structural Ambidexterity on Improving the Quality of Lecturers in Higher Educations in Indonesia: Literature Review - Saing, Bungaran; Saripudin, Saripudin; Istiantoro, Nugraha; Tukiran, Martinus (IJOSMAS, 2021)
A systematic literature review aims to determine the challenges and structural ambidexterity in improving the quality of lecturers at Indonesian universities. Articles were selected through a screening process in 2014-2021. Reviews were conducted on an online database, Google Scholar. There were seven articles reviewed based on the lecturer's quality criteria. Based on the analysis of the article, there are nine challenges to improve the quality of lecturers in universities and structural ambidexterity to improve the quality of university lecturers in Indonesia.